A rapid value chain analysis including agroecological assessment: Olive Oil Value Chain Analysis in El Kef Governorate, North-West Tunisia - Dhehibi, Boubaker; Souissi, Asma; M. Oumer, Ali; Frija, Aymen; Idoudi, Zied; Ouerghemmi, Hassen; Shiri, Zahra; Le, Quang Bao; Alary, Veronique; Rudiger, Udo; Rekik, Mourad; Oueslati-Zlaoui, Meriem; et al. (2024)
This research work was implemented under the CGIAR Initiative on “Transformational Agroecology across Food Land and Water Systems” in the framework of the WP3 “Inclusive Business Models and Financing Strategies” led by the International Center for Agricultural Research in the Dry Areas - ICARDA. The aim of the work package 3 is to develop an inclusive Business Model that facilitates the agroecological transition through potential value chains. The objective of this report is to analyze, map and select the main value chain with potential to integrate the agroecological transition in the Kef-Siliana transect. The methodology is based on secondary data analysis, a rapid value chains analysis, agroecological assessment, focus group discussions and participatory approach with the main stakeholders. A participatory approach was adopted through 4 focus group discussions at the living lab level with all the relevant stakeholders through the organization of two workshops in Kef and Siliana governorates. The selection of the value chains by the members of the living lab was done according to a global evaluation matrix prioritizing the value chains based on a set of predefined criteria (economic, social, and environmental) of impact and feasibility. In the second step of the participatory approach, two workshops on main value chains identification, prioritization and actors mapping took place on December 8th and 15th, 2022 in Siliana and El Kef (North-West Tunisia). The number of participants was 33 and 30 in Kef and Siliana, respectively. In the plenary sessions of the workshops, the attendants were asked to choose the value chains (VC) the most adapted to the region based on economic, social, and environmental criteria. Different agroecological practices such as rotation, crop diversification, forage association, inputs reduction, recycling, etc., are revealed by the farmers interviewed during the focus group discussions. The 13 agroecological principles applied to the value chains selected by the participants are discussed and identified during the focus groups. Finally, the business model proposed based on the participatory approach with the main stakeholders in both locations is olive oil in Kef governorate. The objective of the business model is to encourage the olive producers’ association (SMSA) to produce a labeled olive oil to improve their revenues, enhance livelihoods and create a system of values that includes geographic location.